Young Avengers. - Gillen, Kieron (Marvel now!, 2014)
They say you can never go home. For the Young Avengers, that's not true. They can go home--it's just that if they do, the universe may end. Better not go home then, eh? (Wait, what are you doing, Young Avengers? You've decided to go home?!?) The team takes on the gig to save reality, but is Kate Bishop an enemy in waiting? Is this the last we see of the loveable/ strangle-able Kid Loki?--p. [4] of cover.